SHM_1285831_HST_3D Stone Battle Axe - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a stone battle axe from the Swedish Early Neolithic. Collected from Hallsberg Parish in Närke, Sweden, the axe is currently held in the collections of the National Historical Museum in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=396

Link to Sök I Samlingarna

https://samlingar.shm.se/object/330A0AE4-0C07-429B-83C8-E62D39D53A65?type=object&query=1285831_HST&n=1
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Structured Light Scanning; Swedish Early Neolithic; Hallsberg; 3D Model; Museum Object; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi